RESOLUSI KONFLIK ROMANTIC JEALOUSY PASANGAN SUAMI ISTRI DALAM PRESPEKTIF HADITS KUTUB AL-TIS’AH - Ubaidillah, M. Burhanuddin (USRATUNA: Jurnal Hukum Keluarga Islam, 2021)
Romantic Jealousy or jealousy in a romantic relationship is a relatively common feeling. Romantic Jealousy is a divine decree that cannot be avoided and is not worthy of being hostile. Romantic Jealousy is part of the implication of love and loyalty. Romantic Jealousy is a kind of feeling of worry or fear of losing a life partner, with the presence of a third party who has the ability to influence, seduce and seduce. Romantic Jealousy is a reaction that occurs in a romantic relationship that is being threatened by a third party, both subjective and real, which is usually followed by a fear of losing their partner. When experiencing it, usually the rational system does not work as it should. This article focuses on the study of the romantic jealousy hadiths of the Prophet's wives, especially isyah's romantic jealousy to Umm Salamah, to Ḥafṣah, to Shofiyyah, and to Khadījah as well as Hafsah's romantic jealousy to isyah along with the resolution of the Prophet's conflicts conta